ORIENTASI PERAN EGALITER, KESEIMBANGAN KERJA-KELUARGA DAN KEPUASAN KELUARGA PADA PEREMPUAN YANG BERPERAN GANDA - Hilwa Anwar (Universitas Negeri Makassar, 2015)
Family and work are two important domains that can’t be separated from the life of women with dual role. In this research, work-family study focused on the characteristics of family domain and family satisfaction as the output. Women's perception of family gender roles and work family balance is assumed to have an influence on family satisfaction. Therefore, this research aims to examine the relationship between gender role orientation of family, and work-family balance with family satisfaction of women with dual role. Respondent of this research is 108 women who had married and working in the formal sector, with non-probability sampling as the sample taking technique. Data collection method that is used in this study is a scale and processed by using path analysis. Based on the analysis found that there is a positive relationship between egalitarian gender roles orientation with family satisfaction through work-family balance, and its effective contribution is 18.9%.